2006
DOI: 10.1107/s1600536806005447
|View full text |Cite
|
Sign up to set email alerts
|

N,N′-Bis(3-nitrophenyl)isophthalamide tetrabutylammonium chloride

Abstract: The receptor of the title compound, C14H36N+·Cl−·C20H14N4O6, binds a chloride anion via two N—H⋯Cl hydrogen bonds [N⋯Cl = 3.2367 (14) Å and 3.3239 (15)°].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…The related ditopic ligand 6 , a dichloro analogue of 5 that was synthesized to enhance the hydrogen‐bonding capabilities, readily holds two chloride ions in the two separate binding sites. In the solid state, each Cl − ion is bound by three NH groups: two amide groups (N⋅⋅⋅Cl=3.27 and 3.28 Å) and a pyrrole donor (N⋅⋅⋅Cl=3.07 Å) 18. Crystallization in the presence of n Bu 4 N + F − , however, results in deprotonation of the pyrrole owing to the highly basic nature of F − in acetonitrile, which results in polymeric chains 19…”
Section: Spherical Anionsmentioning
confidence: 99%
“…The related ditopic ligand 6 , a dichloro analogue of 5 that was synthesized to enhance the hydrogen‐bonding capabilities, readily holds two chloride ions in the two separate binding sites. In the solid state, each Cl − ion is bound by three NH groups: two amide groups (N⋅⋅⋅Cl=3.27 and 3.28 Å) and a pyrrole donor (N⋅⋅⋅Cl=3.07 Å) 18. Crystallization in the presence of n Bu 4 N + F − , however, results in deprotonation of the pyrrole owing to the highly basic nature of F − in acetonitrile, which results in polymeric chains 19…”
Section: Spherical Anionsmentioning
confidence: 99%
“…2a, †) showed that a 2 : 2 chloride-receptor complex is formed in the solid state, whereby the chloride anion is bound to two different molecules of 1 via two hydrogen bonds (O/Cl distances of 2.929(3) Å and 2.954(2) Å and O-H/Cl angles of 160(2) and 163(2) ). This 2 : 2 binding stoichiometry is surprising given the fact that crystal structures obtained with structurally similar acyclic isophthalamides usually present a 1 : 1 anion-receptor stoichiometry 37,38 (with few exceptions of 2 : 2 stoichiometry), 39 and might reect the greater rotational exibility of the uorinated alcohol group compared to the amide functionality. It is not clear whether the same 2 : 2 stoichiometry exists in solution or whether it is a crystal packing effect, as the solution based 1 H NMR titrations cannot discriminate between a 1 : 1 and a 2 : 2 stoichiometry and it is possible that both stoichiometries coexist in solution.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…For the design of artificial receptors related to isophthalamide, see: . For related structures, see: Light et al (2006); Kavallieratos et al (1997Kavallieratos et al ( , 1999. For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Considerable attention has been focused on the design of artificial receptors that are able to selectively recognize and sense anion species . Artificial receptors, containing the isophthalamide core function as effective receptors for halide anions in very simple systems (Kavallieratos et al, 1997(Kavallieratos et al, , 1999Light et al 2006). We report here the crystal structure of the title compound, C 20 H 12 Cl 4 N 2 O 2 , (I), related to these types of receptors.…”
Section: S1 Commentmentioning
confidence: 99%